X-Ray Diffraction Characterisation of Crystallinity and Phase Composition in Manganese Oxides Composite Prepared by Molten Salts / Mohd Faiz Hassan and Kok Sheng Chan - Hassan, Mohd Faiz; Sheng Chan, Kok (UiTM Press for the Institute of Research Management & Innovation (IRMI), Universiti Teknologi MARA, 2019)
The manganese oxides composite was synthesised via a simple molten salts method using a purchased MnCl2•2H2O as structuring agent. The structural details of the sample are important to be studied and previously rarely reported. It was characterised using X-ray diffraction (XRD) and data analyses including fitting process were done by Search-Match and Origin software. The Vesta software was used to draw a diagram crystal structure of the as-prepared composite. The experimental results indicated that the composite has two phases, Mn3O4 and MnO2, in value of approximately 74.22% and 25.78%, separately. The composite was highly crystalline with 74.69% compared to 25.31% for amorphous. The crystallite size of the Mn3O4 and MnO2 were calculated in an average of 22 and 24 nm, respectively. However, the lattice strain of the as-prepared composite was obtained between 7.1 x 10-3 and 7.4 x 10-3. The lattice parameters for the Mn3O4 compound was a = 5.705 Å and c = 9.473 Å, whereas a = 9.390 Å, b = 2.477 Å, c = 4.705 Å correspond to the MnO2 compound. The obtained results concluded that the composite containing two different types of system structure (tetragonal and orthorhombic).